In Vitro Characterization of 177Lu-DOTA-M5A Anti-Carcinoembryonic Antigen Humanized Antibody and HSP90 Inhibition for Potentiated Radioimmunotherapy of Colorectal Cancer - Mohajershojai, Tabassom; Jha, Preeti; Boström, Anna; Frejd, Fredrik Y.; Yazaki, Paul J.; Nestor, Marika (Frontiers in Oncology, 2022)
Carcinoembryonic antigen (CEA) is an antigen highly expressed in colorectal cancers, and widely used as a tumor marker. 131I and 90Y-radiolabeled anti-CEA monoclonal antibodies (mAbs) have previously been assessed for radio-immunotherapy in early clinical trials with promising results. Moreover, the heat shock protein 90 inhibitor onalespib has previously demonstrated radiotherapy potentiation effects in vivo. In the present study, a 177Lu-radiolabeled anti-CEA hT84.66-M5A mAb (M5A) conjugate was developed and the potential therapeutic effects of 177Lu-DOTA-M5A and/or onalespib were investigated. 177Lu-radiolabeling of M5A was first optimized and characterized. Binding specificity and affinity of the conjugate was then evaluated in a panel of gastrointestinal cancer cell lines. The effects on spheroid growth and cell viability, as well as molecular effects from treatments were then assessed in several 3D multicellular colorectal cancer spheroid models. Stable and reproducible radiolabeling was obtained, with labeling yields above 92%, and stability retained at least 48 h post-radiolabeling. Antigen-specific binding of the radiolabeled conjugate was demonstrated on all CEA positive cell lines. Dose-dependent therapeutic effects of both 177Lu-DOTA-M5A and onalespib were demonstrated in the spheroid models. Moreover, effects were potentiated in several dose combinations, where spheroid sizes and viabilities were significantly decreased compared to the corresponding monotherapies. For example, the combination treatment with 350 nM onalespib and 20 kBq 177Lu-DOTA-M5A resulted in 2.5 and 2.3 times smaller spheroids at the experimental endoint than the corresponding monotreatments in the SNU1544 spheroid model. Synergistic effects were demonstrated in several of the more effective combinations. Molecular assessments validated the therapy results, and displayed increased apoptosis elevation in several combination treatments. In conclusion, the combination therapy of anti-CEA 177Lu-DOTA-M5A and onalespib showed an enhanced therapeutic effect over the individual monotherapies for the potential treatment of colorectal cancer. Further in vitro and in vivo studies are warranted to confirm the current study findings.